Capital Structure And Firm Value: The Mediating Role Of Profitability - Asmin; Burhanuddin; Anwar; Nurman; Andi Mustika Amin (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
The property and real estate sector is one of the important sectors that contribute to the Indonesian economy, but in the 2021–2024 period, this sector experienced a decline in company value as reflected in market performance. This problem prompted this study, which aims to analyze the effect of capital structure on company value and examine the role of profitability as a mediating variable in property and real estate sector companies listed on the Indonesia Stock Exchange for the 2020–2024 period. This study uses a quantitative approach with the Partial Least Square-Structural Equation Modeling (PLS-SEM) method and the sample was determined through a purposive sampling technique on companies that meet the research criteria. The results of the study indicate that capital structure has a significant negative effect on company value and profitability, while profitability has a significant positive effect on company value and is proven to mediate the effect of capital structure on company value; this finding supports the Trade-off Theory regarding the importance of balance in the use of debt, but also shows limitations in the application of Signaling Theory in the property sector. This study concludes that excessive use of debt can reduce profitability and company value, so companies need to establish an optimal capital structure to maintain financial performance and increase investor confidence.